2011 IEEE International Ultrasonics Symposium 2011
DOI: 10.1109/ultsym.2011.0465
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional myocardial strain estimation from volumetric ultrasound: Experimental validation in an animal model

Abstract: Abstract-Although real-time three-dimensional echocardiography has the potential to allow for more accurate assessment of global and regional ventricular dynamics compared to the more traditional two-dimensional ultrasound examinations, it still requires rigorous testing and validation against other accepted techniques should it breakthrough as a standard examination in routine clinical practice. Very few studies have looked at a validation of regional functional indices in an in-vivo context. The aim of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…More than a decade ago, Papademetris et al 20,49 were the first to report on the in vivo validation of a model-based 3D STE approach against sonomicrometry 20 and opaque MRI markers. 49 In more recent years, different implementations of block matching-based approaches, [50][51][52][53][54] a new implementation of a modelbased approach, 40 and an elastic registration 3D STE approach 56 have been validated in an in vivo setting. All these studies reported moderate to good correlations (r = 0.49-0.91) between regional strain values obtained by 3D STE methods and sonomicrometry 40,51,56 (Table 2).…”
Section: Validation In An In Vivo Experimental Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…More than a decade ago, Papademetris et al 20,49 were the first to report on the in vivo validation of a model-based 3D STE approach against sonomicrometry 20 and opaque MRI markers. 49 In more recent years, different implementations of block matching-based approaches, [50][51][52][53][54] a new implementation of a modelbased approach, 40 and an elastic registration 3D STE approach 56 have been validated in an in vivo setting. All these studies reported moderate to good correlations (r = 0.49-0.91) between regional strain values obtained by 3D STE methods and sonomicrometry 40,51,56 (Table 2).…”
Section: Validation In An In Vivo Experimental Settingmentioning
confidence: 99%
“…49 In more recent years, different implementations of block matching-based approaches, [50][51][52][53][54] a new implementation of a modelbased approach, 40 and an elastic registration 3D STE approach 56 have been validated in an in vivo setting. All these studies reported moderate to good correlations (r = 0.49-0.91) between regional strain values obtained by 3D STE methods and sonomicrometry 40,51,56 (Table 2). However, care should be taken in interpreting and comparing those results, as not all of the studies reported strain values corresponding to a local cardiac coordinate system (i.e., RS, LS, and CS).…”
Section: Validation In An In Vivo Experimental Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar experiments were performed previously using a CFFD model. In phantom data, correlations were 0.98, 0.96 and 0.92 for RR , LL and CC respectively [4], while correlations in sheep data were 0.21, 0.63 and 0.60 respectively [9]. Seo et al reported similar findings in an in-vivo setup using a state-of-the-art commercially available 3D speckle tracking method that typically relies on block-matching based algorithms to track tissue motion (r=0.59-0.70 for RR , r=0.65-0.68 for LL and r=0.71-0.78 for CC [10]).…”
Section: Discussionmentioning
confidence: 91%
“…For a full description of the experimental protocol in these setups, the reader is referred to [4] and [9] respectively. Briefly, volumetric data was recorded in gel phantoms and in 5 open-chest sheep, from an apical view using a GE VividE9 equipped with a 2.5 MHz transducer (3V) at a frame rate of 13-17 Hz and 25-32 Hz respectively.…”
Section: Methodsmentioning
confidence: 99%